2022
DOI: 10.3847/1538-4357/ac4fbe
|View full text |Cite
|
Sign up to set email alerts
|

A Partial Filament Eruption in Three Steps Induced by External Magnetic Reconnection

Abstract: We present an investigation of partial filament eruption on 2012 June 17 in the active region NOAA 11504. For the first time, we observed the vertical splitting process during the partial eruption with high-resolution narrowband images at 10830 Å. The active filament was rooted in a small δ-sunspot of the active region. Particularly, it underwent the partial eruption in three steps, i.e., the precursor, the first eruption, and the second eruption, while the latter two were associated with a C1.0 flare and a C3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…For example, Xue et al (2023) reported a filament splitting event caused by the reconnection of emerging magnetic fields with one leg of the pre-eruption filament. Similar splitting processes driven by such reconnection with surrounding structures could also further result in partial eruptions of solar filaments (Chen et al 2018;Monga et al 2021;Dai et al 2022).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Xue et al (2023) reported a filament splitting event caused by the reconnection of emerging magnetic fields with one leg of the pre-eruption filament. Similar splitting processes driven by such reconnection with surrounding structures could also further result in partial eruptions of solar filaments (Chen et al 2018;Monga et al 2021;Dai et al 2022).…”
Section: Introductionmentioning
confidence: 93%
“…Previous high-resolution observations have revealed that solar filaments exhibit a wide range of eruptive dynamics. Gilbert et al (2007) developed observational definitions for three types of filament eruptions: (1) "full eruptions," where the magnetic structure and material of the pre-eruptive filament completely escape the Sun; (2) "failed eruptions," where the eruptive process of the filament is suddenly halted in the low corona, with none of the lifted filament material nor magnetic structure escaping the Sun (Ji et al 2003;Török & Kliem 2005;Myers et al 2015;Li & Ding 2017;Yan et al 2020); and (3) "partial eruptions," where only part of the filament magnetic structure and/or material is eventually expelled (Gilbert et al 2000;Bi et al 2015;Zhang et al 2015;Chen et al 2018;Dai et al 2022). Among the three types, filament partial eruptions are relatively more complicated, because the involved preeruption filament does not evolve as a whole and shows nonuniform characteristics in terms of magnetic topology and/ or plasma motion.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic reconnection can sometimes establish or alter the magnetic structure of a filament (DeVore et al 2005;Li et al 2018;Xue et al 2019;Yang et al 2021), and can trigger a filament to erupt through the interaction between the filament's magnetic fields and its surrounding magnetic structures (Li et al 2016;Xue et al 2016;Huang et al 2018). In partial eruptions, filaments are usually split by reconnection occurring either above or within the magnetic structure; the upper part erupts into the interplanetary space while the lower part remains in the lower atmosphere (Gilbert et al 2001;Liu et al 2018;Monga et al 2021;Dai et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, the interaction of a filament and nearby emerging magnetic fields leads to its reconfiguration and eruption (Li et al 2022a). Recently, Dai et al (2022) showed that interaction between a filament and nearby loops induces the filament to split and erupt. Due to the observational limitation, detailed observations about the dynamics of the structures between two interacting filaments are rare.…”
Section: Introductionmentioning
confidence: 99%